A Study of Using Waste Tire Cord Fabric in Asphalt Concrete - นกแก้ว นิรชร (Frontiers in Engineering Innovation Research, 2009)
Waste Tire Cord Fabric, the residue from wasted tire particles process in union commercial development Co, Ltd. Phrapradaeng, Samuthprakarn, was used to add some aggregate in asphalt concrete. Limestone from Hanjarearn Enterpise Chiang Rai quarry, Chiang Rai and basalt from Buri Ram Ruchda quarry, Buri Ram and asphalt cement grade 60-70 were used. From series of experiments, it was concluded that the most suitable mix proportions of Hot Bin I :2:3:4 which produced asphalt concrete of qualities complied with Department of Highways Standard was 43 : 30 : 14: 13 with asphalt cement of 5.1 percent by mass of aggregate and waste tire cord fabric of 0.2 percent by mass of aggregate when using limestone as aggregates; and48: L0 21 :21 with asphalt cement of 5.6 percent by mass of aggregate and waste tire cord fabric of 0.2 percent by mass of aggregate when using basalt as aggegates. Strenght indexs of above asphalt concrete mixs were 78.8 and 77.l percent respectively, which are compiled with the Department of Highways Standard, and this material is more stable than the normal asphalt concrete.